2006
DOI: 10.1016/j.gene.2005.12.012
|View full text |Cite
|
Sign up to set email alerts
|

NFATc1 regulation of the human β3 integrin promoter in osteoclast differentiation

Abstract: The transcription factor NFATc1 plays an essential role in transducing signals from RANKL in osteoclast differentiation. To date, however, the specific transcriptional targets of NFATc1 are unknown. Expression of the beta3 integrin is required for normal osteoclast function. We therefore examined the role of NFATc1 in human beta3 integrin expression in osteoclast differentiation. Analysis of the mouse and human beta3 gene promoters revealed considerable sequence homology across a 1.3 kb region upstream of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
103
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(120 citation statements)
references
References 38 publications
13
103
1
2
Order By: Relevance
“…S4 A-E). Consistent with inhibition of Cn, CsA treatment significantly decreased induction of the NFATc1-dependent integrin β3 gene (34,35) by TNF (Fig. S4B).…”
Section: Tnf Triggers a Differentiation Program In Human Macrophages Viasupporting
confidence: 62%
“…S4 A-E). Consistent with inhibition of Cn, CsA treatment significantly decreased induction of the NFATc1-dependent integrin β3 gene (34,35) by TNF (Fig. S4B).…”
Section: Tnf Triggers a Differentiation Program In Human Macrophages Viasupporting
confidence: 62%
“…49,50) Our results indicated that, although tetrandrine had little effect on the initial induction of NFATc1 by sRANKL, it did inhibit the subsequent auto-amplification of NFATc1. All NFAT family members, including NFATc1, are mainly regulated by the serine/threonine phosphatase calcineurin, which is activated by intracellular Ca…”
Section: Discussionmentioning
confidence: 69%
“…Because NFATc1 as an upstream transcription factor to regulate integrin b3 expression, DICAMmediated inhibition of integrin b3 expression may be due to delayed osteoclast differentiation. (27,28) However, we cannot rule out the possibility of accelerated endocytosis and degradation of integrin b3 by DICAM. More studies are needed to understand the precise molecular mechanism of DICAM's gene expression during osteoclastogenesis.…”
Section: Discussionmentioning
confidence: 94%